TECHNICAL AND ECONOMIC SUBSTANTIATION FOR SELECTION OF THE METHOD OF ELECTRO-THERMAL PROTECTION OF SOLAR PANELS IN THE SPACECRAFT POWER PLANTS - HILORME, Tetiana; NAKASHYDZE, Liliya (Herald of Khmelnytskyi National University. Technical sciences, 2022)
An actual scientific and practical problem of the energy sustainable development of space activities is the choice of solar cells for the uninterrupted supply of energy in the power plants of space vehicles. The operational risks of solar cells in the conditions of space activity are analyzed. It is proposed to use the method of evaluating the analytical hierarchical process of providing electrothermal protection of solar cells in power plants of space vehicles, which allows obtaining a set of optimal options. The selection of criteria for the parameters selection of electrothermal protection of solar cells, which take into account the specific operational risks of power plants in outer space, is substantiated: ensuring uninterrupted operation of solar cells; availability of service in extraordinary situations; lifetime of solar cells; the cost of solar panels; technical security; weight and size indicators. Five alternative options for electro-thermal protection of solar cells were chosen, which, unlike the existing ones, take into account all phases of the life cycle during the implementation of space activities and significantly increase operational characteristics. It is argued that the chosen optimal alternative "Solar cells with protection based on resettable fuses" will allow increasing the active service life and, as a result, reducing the number of repairs (current and capital) of solar cells in the conditions of space activities. It is argued that the introduction of this option can achieve an increase in operational criteria: service availability in non-staff situations by 26%, the term of active operation by 20% and technical safety by 24%. The article defines the directions for the further development of this technique as the possibility of developing scenarios for the operation of solar cells in power plants of space vehicles based on the change and interaction of parameters (concepts).
Keywords: solar cell; space vehicle; electrothermal protection; service life; technical safety